IDENTIFIKASI KETIDAKTEPATAN KODE DIAGNOSIS PENYAKIT DEMAM BERDARAH DENGUE BERDASARKAN HASIL PEMERIKSAAN KLINIS DAN LABORATORIUM PADA REKAM MEDIS RAWAT INAP RS WAVA HUSADA - Suryandari, Endang Sri Dewi Hastati; Masliya, Fitri Setyawati Nur (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2025)
The completeness of medical information such as the results of clinical and laboratory examinations, greatly influences the accuracy of the disease diagnosis code. This study aims was to identify and classify inaccuracies of the Dengue Haemorrhagic Fever (DHF) disease’s diagnosis code based on the results of clinical and laboratory examinations in inpatient MRDs at Wava Husada Hospital. The research’s design was descriptive with a retrospective approach. The research population were 482 MRDs for inpatient DHF. The sample used was 83 MRDs with a simple random sampling technique. Data collection using document review in the coding section and using checklist sheet instruments. The results showed that the accuracy of the DHF diagnosis code based on clinical and laboratory examinations results was 62.7% and the incorrect code was 37.3%. The classification of inaccurate diagnosis codes were caused by incorrect assignment of diagnosis codes (54.9%), clinical examination results did not meet the requirements for establishing a DHF diagnosis (41.9%), and laboratory examination results did not meet the requirements for establishing a DHF diagnosis (3.2%). It is necessary to improve the accuracy of coding officers in analyzing patient medical information.